2015
DOI: 10.3389/fphys.2015.00095
|View full text |Cite
|
Sign up to set email alerts
|

Midgut serine proteases and alternative host plant utilization in Pieris brassicae L.

Abstract: Pieris brassicae L. is a serious pest of cultivated crucifers in several parts of the world. Larvae of P. brassicae also feed prolifically on garden nasturtium (Tropaeolum majus L., of the family Tropaeolaceae). Proteolytic digestion was studied in larvae feeding on multiple hosts. Fourth instars were collected from cauliflower fields before transfer onto detached, aerial tissues of selected host plants in the lab. Variable levels of midgut proteases were detected in larvae fed on different hosts using protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 94 publications
(120 reference statements)
2
26
0
Order By: Relevance
“…Likewise, it had been reported that the combination of feeding deterrents showed feeding deterrent habituation in other insects and the combination of saponins I and II may also slow down feeding deterrent habituation in P. xylostella . Nevertheless, saponins I and II contain similar chemical structures; cross habituation might be easier as compared to compounds with different chemical structures, which also indicate the synthesis of saponin-II could be after that of saponin-I [216,217,218,219].…”
Section: Biological Significance Of Saponinsmentioning
confidence: 99%
“…Likewise, it had been reported that the combination of feeding deterrents showed feeding deterrent habituation in other insects and the combination of saponins I and II may also slow down feeding deterrent habituation in P. xylostella . Nevertheless, saponins I and II contain similar chemical structures; cross habituation might be easier as compared to compounds with different chemical structures, which also indicate the synthesis of saponin-II could be after that of saponin-I [216,217,218,219].…”
Section: Biological Significance Of Saponinsmentioning
confidence: 99%
“…The further predict function of DEGs was searched against the eukaryotes (KOG) and prokaryotes (COG) database. Before KOG and COG classification, the RNA sequences of unigenes were transformed into protein sequences with TransDecoder software, which was a part of Trinity (Kumar et al., ). Overall, a total of 502 DEGs were assigned to 25 COG groups, and 908 DEGs were assigned to 25 KOG groups with an e‐value cutoff of 1 × 10 −5 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, BoPI, a trypsin inhibitor reported from wild cabbage, reduced larval growth of Heliothis virescens but not Brassicaceae pests that were presumably adapted to the inhibitor (Pulliam, Williams, & Broadway, ). CfTI, a trypsin inhibitor from cauliflower, was ineffective in inhibiting the proteases of larvae fed cauliflower (Giri et al., ), indicating the presence of CfTI‐insensitive midgut trypsins (Kumar, Bhardwaj, Kumar, & Mazumdarleighton, ). Therefore, PIs from the nonhost plants might be an alternative and promising resource for crop‐protection strategy, despite the fact that those influence on insect midgut physiology and responding mechanism remained poorly understood (Liao et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A common mechanism of adaptation to phytophagy and wide diet breadth in several phytophagous pests involves production of insensitive, compensatory and/or degradative proteases in larval guts upon chronic ingestion of host antifeedants, like plant protease inhibitors, PPI [ 18 ]. Adaptation to ingested protease inhibitors from different plant families including Brassicaceae and Tropaeolaceae has been reported in larvae of various Pieris species [ 12 , 19 , 20 ]. These plant families also contain distinct classes of glucosinolates that influence herbivory by reacting with plant myrosinases to produce toxic isocyanate moieties, referred to as the “mustard oil bomb” [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A unique adaptation to herbivory in Pieris species involves production of nitrile-specifier protein (NSP) in the larval gut to defuse the “mustard oil bomb” rendering these insects as specialist feeders on plant families containing glucosinolates and in fact, showing preferential oviposition on these hosts [ 5 , 23 – 25 ]. Mechanisms of adaptation to variable nutrient quality, multiple dietary antifeedants and secondary metabolites in diverse host plant species can influence complex traits like relative larval performance of Pieris species at both interspecific and intraspecific levels [ 12 , 13 , 25 – 28 ]. While the association of distinct glucosinolates profiles in host plants and larval performance of Pieris species is documented [ 6 , 10 , 29 ] the role of gut serine proteases in rapid dietary adaptations during a reciprocal switch of larvae to an alternate host-plant type is not as well-characterized.…”
Section: Introductionmentioning
confidence: 99%